Human Personality In The Era Of Globalization From Da'wah Perspective - Hendra Wijaya (CV. Syntax Corporation Indonesia, 2023)
The purpose of this research is to discover how the concept of human personality is based on age generations in the era of globalization and the challenges faced by each of these personalities in dealing with this era as well as the concept of the da'wah approach for each personality. This research is included in the type of library research (Library research) because the data sources come from written sources, both directly related to the material being studied and indirectly. Then in terms of presentation this material is descriptive analysis in nature, because this research seeks to describe the Concept of Human Personality based on the age generation in the Globalization Era and the challenges faced by each of these personalities in facing that Era as well as the Concept of Da'wah Approach for each personality. Based on the results of the analysis it can be concluded that Human Personality is different from one another based on their age or generation, so that the challenges faced by each personality generation are different in dealing with all phenomena that exist in the Globalization Era, and the Da'wah Approach must also adapt to their personality in responding to things that exist in the Era of Globalization.